Prepositions in English and Their Alternatives in Uzbek Language - Yangibaeva Nazira; Guldana Konratbaeva (Genius Journals, 2022)
This article provides information about prepositions in English and their alternatives in Uzbek.
Keywords: International language; prepositions; analytical language